Capacity Development of Social Workers in Enhancing Social Welfare Service Delivery - Eka Nurwahyuliningsih; Indah Pusnita (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study examines social workers’ capacity development in enhancing social welfare service delivery at Sentra Budi Perkasa Palembang. The study contributes to the literature by explaining the relationship between social welfare human resource development, social workers’ competencies, service quality, and welfare outcomes for beneficiaries. Unlike previous studies that primarily describe human resource development as a set of training activities, this research conceptualizes it as a continuous institutional process. A qualitative case study approach was employed. Data were collected through in-depth interviews, non-participant observation, and document analysis involving 10 purposively selected informants, including managerial staff, social workers, support personnel, and beneficiaries. Data validity was ensured through source and method triangulation as well as member checking. The findings indicate that orientation programs, training, competency certification, and further education improve social workers’ understanding of tasks, assessment skills, case management capacity, interprofessional collaboration, and adaptive service delivery. However, program effectiveness remains limited because post-training evaluation is not systematically implemented and digital competency development has not yet become a strategic institutional priority. The study concludes that capacity development should extend beyond training participation and focus on strengthening competencies, improving service quality, and enhancing beneficiaries’ social functioning.